Spatial Modeling of MSME Risk Based on Webgis with The Integration of Multidimensional Factor Analysis in Majene Regency - Deril, Virda Evi Yanti; Astinawaty; Mahful, Rafid; Mujahid, Laode Muh. Asfan; Khatiran, Hamdan; Nurhalisa (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2026)
This research investigates and maps potential risks for Micro, Small, and Medium Enterprises (MSMEs) in Majene Regency, analyzing aspects of Human Resources (HR), capital, production, marketing, and law/legality. MSMEs are crucial to the regional economy , but they often face significant risks that hinder growth. This problem is worsened by a lack of spatial understanding of these vulnerabilities , which makes government interventions and development initiatives less effective. This study aims to spatially model and map MSME risks by integrating multidimensional factor analysis with WebGIS. The methodology involves four stages: (1) acquiring primary and secondary data related to the five risk dimensions; (2) using descriptive statistical and cluster analysis to categorize MSMEs; (3) applying risk factor scoring and weighting analysis to determine potential risk levels ; and (4) developing spatial modeling and GIS for risk visualization. The research results in a classification of MSMEs based on risk levels (high, medium, low), which is presented on a WebGIS platform to allow interactive spatial visualization. The findings are intended to provide a basis for more informed decision-making in the development of MSMEs in Majene Regency.